Digitalization in urban planning: a framework to realize smart cities - D'Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2025)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always remaining in the groove of rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of continuously updating emerging topics concerning relationships between urban planning, mobility and environment, through a collection of short scientific papers written by young researchers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Urban strategies, programmers and tools section presents presents the different strategies and tools that guide the digitalization of urban planning. The contribution explores how innovation is increasingly important in the current definition of urban planning processes. The policies and programs needed to support the transition towards smart cities, more efficient, sustainable and citizen-oriented, are outlined.The analysis illustrates the key strategies and main programs implemented by the European Union and other International Organizations to promote the digital transformation of cities to make them "smart" and sustainable. Concrete examples are presented of cities that have successfully implemented these strategies, addressing challenges such as climate change and resource management, demonstrating how digitalization can create more liveable and resilient urban spaces.